2019
DOI: 10.1016/j.jechem.2019.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing carbon/carbon supercapacitors in aqueous alkali sulfates electrolytes

Abstract: a b s t r a c tNeutral aqueous alkali sulfate has shown great interests for developing environmentally friendly high voltage and high energy supercapacitors. This work focuses on systematically investigating the properties of symmetric carbon/carbon supercapacitors in neutral aqueous alkali sulfates. At room temperature, the largest power and energy density were obtained with K 2 SO 4 electrolyte due to the smallest cation dimensions and highest electrical conductivity. At low temperature, aqueous Li 2 SO 4 el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…This strong potential decay of the negative electrode can be explained by the contribution of redox processes related to the electrochemical reduction of water at large negative potentials. These redox processes result in the generation of hydroxyl anions, which causes a local shift of pH in the pores of the negative electrode [51]. Since the concentration of the NaNO 3 electrolyte is 1 mol L −1 , which is not very high, the local concentration of OH - generated due to the reduction of water is immediately shifted due to the dilution effect and a consequent shift of local pH to a neutral value occurs, which results in high self-discharge at the negative electrode, as explained elsewhere [52,53].…”
Section: Resultsmentioning
confidence: 99%
“…This strong potential decay of the negative electrode can be explained by the contribution of redox processes related to the electrochemical reduction of water at large negative potentials. These redox processes result in the generation of hydroxyl anions, which causes a local shift of pH in the pores of the negative electrode [51]. Since the concentration of the NaNO 3 electrolyte is 1 mol L −1 , which is not very high, the local concentration of OH - generated due to the reduction of water is immediately shifted due to the dilution effect and a consequent shift of local pH to a neutral value occurs, which results in high self-discharge at the negative electrode, as explained elsewhere [52,53].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, electrochemical stability of aqueous electrolytes is limited by the water decomposition voltage (theoretically at 1.23 V) and this is the major obstacle on the way to wide commercialization of these systems. Nonetheless, for systems operating with neutral electrolytes (with pH around 7) such as 0.5-2 mol/L solutions of Li-, Na-, K2SO4 or 1-5 mol/L Li-, Na-, KNO3 effective operating voltages up to 1.9 V have been reported 34,39,[66][67][68][69][70][71][72] .…”
Section: Basic Principles Of Electrochemical Capacitorsmentioning
confidence: 99%
“…Previous reports have demonstrated that the optimization of the size, structure and distribution of pore is an efficient way to enhance the electrochemical performances of carbon-based elec-trode materials [20][21][22] . Owing to the existence of lots of oxygen in the carbon precursor and the formation of oxygen functional groups in the carbon matrix during activation process, influence of the surface chemistry of porous carbon also cannot be negligible [23] .…”
Section: Introductionmentioning
confidence: 99%